Novel Trocars and Suspension System Application in Gasless Transoral Endoscopic Thyroidectomy Vestibular Approach Oral Endoscopic Surgery - Fang, Jing; Liu, Jianjun; Zheng, Xucai; Wang, Shengying (Frontiers in Oncology, 2021)
In the current study, we reported our initial experience of gasless TOETVA by novel trocars and suspension system. Between February 2019 to April 2020, thyroid cancer patients with indicated central lymph node metastasis by imaging examination who had received gasless TOETVA by our designed trocars and suspension system in The First Affiliated Hospital of University of Science and Technology of China were reviewed. A total of 95 thyroid cancer patients that received gasless TOETVA were included in this analysis. Of note, 73 cases underwent one-sided lobectomy and the remaining 22 cases underwent total thyroidectomy. All thyroid cancer patients underwent central lymph node dissection (CND). The average total examined lymph nodes number was 8.55±5.67 per individual. No serious complications that occurred during or after the operation besides of 1 patient had short-term recurrent laryngeal nerve (RLN) deficit and 1 patient had delayed postoperative bleeding. In conclusion, the use of novel trocars and suspension system can effectively improve the safety and efficacy of TOETVA.